Molecular Phylogeny of Giant Clams Based on Mitochondrial DNA Cytochrome C Oxidase I Gene - AGUS NURYANTO; DEDY DURYADI; DEDI SOEDHARMA; DIETMAR BLOHM (Bogor Agricultural University, Indonesia, 2007)
There is an uncertainty for the relationships among giant clam species of Tridacninae, in particular among species belongs to subgenus Chametrachea i.e. Tridacna crocea, T. maxima, and T. squamosa based on different genetic markers. This study examined the relationships among three species within subgenus Chametrachea compared to the previous studies. Neighbour Joining, Maximum Parsimony and Maximum Likelihood tree were constructed based on 455 bp of the mitochondrial DNA cytochrome c oxidase I gene from T. crocea, T. squamosa, T. maxima, T. gigas, and several sequences derived from Genbank for the outgroups. The results showed that giant clams formed a monophyletic group. Within Tridacna group, T. crocea was more closely related to T. squamosa than to T. maxima and they formed a monophyletic group. T. crocea and T. squamosa were sister taxa and sister group to T. maxima and T. gigas. Close affinity between T. crocea and T. squamosa was also supported by high similarity on nucleotide level (94.30%) and concordant with the results of the previous studies using mitochondrial 16S rRNA and nuclear 18S rRNA. Key words: phylogenetic relationships, Chametrachea, cytochrome c oxidase I